Evaluation of Fish Silage as a Protein Source in the Diet for River Catfish Mystus Nemurus (C. & V.) - Hasan, Bustari (2001)
A series of experiments was conducted to determine: 1) optimal dietary energy and protein levels for maximum growth of Mystus nemurus (C. & V.), 2) preparation and nutritional quality of fish silage, 3) optimal inclusion levels of fish silage replacing fishmeal in the fish diets, 4) digestibility values of dietary fish silage by fish. Eight experimental diets were formulated to contain four energy levels (2.75, 3.00, 3.25 and 3.50 kcal DE/g) at each of the two protein le vels (38% and 42%), and fed to groups of fingerlings (1.88-213 g) for 10 weeks). It was found that the diet containing 3.25 kcal DE/g and 42% protein (7.74 kcal DElg protein) produced the best growth and food utilization. Five fermented silage and one acid silage were made from short-bodied mackerel (Rastrelinger brachysoma). The fermented silage were prepared by the addition of molasses with different fermentation starters to fish mince, namely: LBPN (80% fish + 15% molasses + 5% Lactobacillus pentosus pure culture), LBPL (80% fish + 15% molasses + 5% Lactobacillus plantarum pure culture), LFBS (70% fish + 15% molasses + 15% liquid fermented bamboo shot), ALPN (70% fish + 15% molasses + 15% aged Lactobacillus pentosus silage), ALPL (70% fish + 15% molasses + 15% aged Lactobac illus plantarum silage). Acid silage (FAS) was made by addition of 3% (w/w) of formic acid to fish mince. These silage were stored at room temperature for 60-180 days. All silage were stable in pH « 4.5), and no spoilage odor was detected through out the storage duration. Nutritional quality of the silage varied with preparation methods. Fermented silage, especially LBPN was more desirable due to less non-protein nitrogen production than acid silage. Fermented and acid fish silage were co-dried with soybean meal (1:1 dry weight basis) and the mixtures were incorporated in fish diets at various levels to substitute fishmeal. Eight test diets (42% protein and 4.20 kcal GE/g) were formulated to contain co-dried fermented fish silage (CFS) and co-dried acid fish silage (CAS) as a replacement for fishmeal. Four of the test diets were composed of CFS at the inclusion levels of 15% (CFS-l ), 30% (CFS-2), 45% (CFS-3), and 60% (CFS-4); and the other four diets were composed of CAS at the inclusion levels of 15% (CAS-I), 30% (CAS-2), 45% (CAS-3), and 60% (CAS-4). A control diet (C) was prepared with 60% fishmeal without fish silage. The diets were fed to Mystus nemurus fingerlings for 10 weeks. One percent of chromium oxide (Cr203) was included in the diets for diet digestibility detennination. The losses of dry matter (LDM) of the diets after lO and 30 minutes in the water (LDM-lO min and LDM-30 min) were 2.3 1 -4.47% and 8 . 1 9- 1 8.58%, respectively for CFS diets, 2.40-4.5 1 % and 9.32- 1 8.26%, respectively for CAS diets and 2. 1 2 and 6.43%, respectively for control diet. The pH values were 6.57-5.78 for CFS diets, 5.64-4.96 for CAS diets and 6.78 for control diet. The essential amino acid profiles (AlE ratio) of both CFS and CAS diets were comparable to AlE ratio of Mystus nemurus. Apparent dry matter, protein and energy digestibility values for both CFS and CAS diets were similar to the control diet. Inclusion of CFS in fish diets up to 45% did not affect growth perfonnance as compared to control diet. However inclusion of more than 15% CAS in fish diets reduced growth perfonnance.